Competing Technologies and Lock-in by Random Events - Elettra Agliardi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
In this paper we study the choice of competing technologies with increasing returns occasioned by learning-by-doing and learning-by-using phenomena. We study under what circumstances one technology can achieve a monopoly and eventually take the whole market by formulating a firm's optimal decision problem, when both uncertainty and increasing returns to adoption are present, In contrast with Arthur (1989) we allow agente to learn: the formulation of the decision problem takes into account the revision of the probabilities on the future states of the adoption process, according to a version of the two-armed bandit problem.
Keywords: 330